1999
DOI: 10.1302/0301-620x.81b1.8928
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal movement

Abstract: We present the first study in vivo of meniscal movement in normal knees under load. Using an open MR scanner, allowing imaging in physiological positions in near to real-time, 16 young footballers were scanned moving from full extension to 90 degrees flexion in the sagittal and coronal planes. Excursion of the meniscal horns, radial displacement and meniscal height were measured. On weight-bearing, the anterior horn of the medial meniscus moves through a mean of 7.1 mm and the posterior horn through 3.9 mm, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(43 citation statements)
references
References 0 publications
3
39
0
1
Order By: Relevance
“…Chronic and repetitive hyper-flexion of the knee under weight-bearing may lead to excessive pressure on the meniscus posterior root and its subsequent impingement and degeneration4,11,14). A controlled clinical study is required to scientifically substantiate this hypothesis.…”
Section: Clinical Characteristics Of Mmprtmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic and repetitive hyper-flexion of the knee under weight-bearing may lead to excessive pressure on the meniscus posterior root and its subsequent impingement and degeneration4,11,14). A controlled clinical study is required to scientifically substantiate this hypothesis.…”
Section: Clinical Characteristics Of Mmprtmentioning
confidence: 99%
“…Posterior root tear tends to occur more in the medial than lateral meniscus. This may be because, during knee flexion, the lateral meniscus moves posteriorly by 19 mm on average, whereas more limited movement of an average of 4 mm occurs in the medial meniscus; thus, the latter becomes more vulnerable to impingement between the femoral condyle and tibial plateau, which, in turn, leads to an increased risk of meniscal damage4,15).…”
Section: Clinical Characteristics Of Mmprtmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, both the ACL deficient and healthy control participants were found to have less than 2 mm of posterior movement of the posterior horns and those values are similar to those found within this study (Table 8). Another study done by Vedi et al [29] examined healthy participants that were standing in an open MRI at 0.5 T at full knee extension and 90 degrees of knee flexion. This study found that in the anterior-posterior direction the lateral meniscus moved more than the medial, and the anterior horns move more than the posterior horns.…”
Section: Discussionmentioning
confidence: 99%
“…The subject was imaged early in the morning and had been unloaded for 30 minutes prior to imaging to minimize a full day of weight bearing. This was done to preserve the native geometry of the cartilage and menisci, as the geometries of these tissues have been reported to change due to body weight loading (Herberhold et al 1999;Vedi et al 1999;Gründer et al 2000;Nishii et al 2008). This may have prevented erroneous measurement of the ACL length at full knee extension, which is required in our subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%